THE NEO-LIBERAL REVOLUTION - Hall, Stuart (Cultural studies (London, England), 2011)
This essay discusses neo-liberalism as a hegemonic process, offering an interpretation of the past 40 years of British political developments. Reprinted by permission of Routledge, Taylor and Francis Ltd.